Effects of salinity and variety on yield contributing characters and yield of Red amaranth - Hossain, Md Shahdat; Alam, ABM Shafiul; Bipa, Momtahina; Rahman, Md Sefaur; Siddeka, Sharifa (Research in Agriculture Livestock and Fisheries, 2019)
An experiment was conducted to evaluate the effects of salinity and variety on yield and yield contributing characters of Red amaranth at Horticulture Farm of Bangladesh Agricultural University, Mymensingh. The experiment consisted of three varieties viz; Altapety, RM, Deshi and four levels of salinity viz; 0mM, 25mM, 50mM and 75mM. The experiment was laid out following RCBD with three replications. Variety had significant effect on yield characters and yield. The highest average weight of plant (9.69 g/pot), highest average root weight (2.13 g/pot), highest average root length (10.28 g/pot) and highest yield per pot (237.08g) were found from the variety Altapety and the lowest average weight of plant (7.67 g/pot), lowest average root weight (2.03 g/pot), lowest average root length (8.83 g/pot) and yield per pot (198.58g) were found from the variety RM. Salinity had significant effect on yield characters and yield. The highest average weight of plant (10.22 g/pot) was recorded from the variety Altapety at the application of 25mM NaCl, highest average of root weight (2.27 g/pot) was recorded from the variety Altapety at the application of 25mM NaCl, highest average of root length (10.29 g/pot) was recorded from the variety Altapety at the application of 25mM NaCl and yield (259.56g/pot) were found from the application of 25mM NaCl. The lowest average weight of plant (6.93 g/pot) was recorded from the variety RM at the application of 75mM NaCl solution, lowest average of root weight (1.78 g/pot) was recorded from the variety RM at the application of 75mM NaCl solution, lowest average of root length (8.12g/pot) was recorded from the variety RM at the application of 75mM NaCl solution and yield per pot (154.44g) were found from the application of 75mM NaCl. Res. Agric., Livest. Fish.6(2): 271-278, August 2019